2001
DOI: 10.1128/aem.67.6.2404-2409.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of 4-Hydroxybenzoic Acid Esters (Parabens) and Their Aerobic Transformation into Phenol by the Resistant Enterobacter cloacae Strain EM

Abstract: Enterobacter cloacae strain EM was isolated from a commercial dietary mineral supplement stabilized by a mixture of methylparaben and propylparaben. It harbored a high-molecular-weight plasmid and was resistant to high concentrations of parabens. Strain EM was able to grow in liquid media containing similar amounts of parabens as found in the mineral supplement (1,700 and 180 mg of methyl and propylparaben, respectively, per liter or 11.2 and 1.0 mM) and in very high concentrations of methylparaben (3,000 mg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 28 publications
4
55
0
1
Order By: Relevance
“…Previous study has shown PHBA was refractory to anaerobic biological treatment [39], leading to little change of PHBA in anaerobic tank and anoxic tank. Additionally, it is reported that the first step of parabens degradation was the hydrolysis of the ester bond to produce PHBA under aerobic condition [40]. Therefore, this result suggests that some PHBA, the main microbial degradation metabolite of parabens, was formed by degradation of parabens during the activated sludge treatment, which resulted in the increase of PHBA levels in oxic tank and secondary clarifier.…”
Section: Analytesmentioning
confidence: 90%
“…Previous study has shown PHBA was refractory to anaerobic biological treatment [39], leading to little change of PHBA in anaerobic tank and anoxic tank. Additionally, it is reported that the first step of parabens degradation was the hydrolysis of the ester bond to produce PHBA under aerobic condition [40]. Therefore, this result suggests that some PHBA, the main microbial degradation metabolite of parabens, was formed by degradation of parabens during the activated sludge treatment, which resulted in the increase of PHBA levels in oxic tank and secondary clarifier.…”
Section: Analytesmentioning
confidence: 90%
“…Caffeic acid has anti-diabetic [50], antioxidant [62], anti-inflammatory and photo-protective [63] activities. 4-Hydroxybenzoic acid esters (also called parabens), are widely used as antimicrobial agents in a large variety of food, pharmaceutical, and cosmetic products due to their excellent antimicrobial activities, low toxicity and stability over a wide pH range [64]. 4-Hydroxybenzoic acid has antifungal, anti-mutagenic, anti-sickling, estrogenic and antimicrobial [62] activities.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning and end of the 2-h incubation, aliquots were removed and heated immediately to 80°C for 10 min in order to prevent further enzymatic degradation of the parabens. The amount of parabens remaining in the samples and the appearance of p-hydroxybenzoic acid was then analyzed by high-performance liquid chromatography as previously described (26). The presence of homologues of prbA in selected strains was determined by touchdown PCR with the primers and conditions specified above.…”
Section: Methodsmentioning
confidence: 99%
“…The amplified gene was ligated into the pGEM-T Easy vector and transformed into competent E. coli DH5␣ cells. The hydrolysis of 600 mg of methyl paraben liter Ϫ1 (4.0 mM) in TSB growth medium was monitored at 37°C as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation